Assessing the Synergistic Anticancer impact of Metronidazole and Ciprofloxacin in Cervical Cancer: MAPK-RAS Pathway as a Key Mechanism - Awn, Anas K.; Arean, Aiad Gaber; Findakly, Sura Basil; Yasin, Youssef Shakuri; Jumaa, Azal Hamoody (Asian Pacific Journal of Cancer Biology, 2026)
Objective: This study assessed the anticancer impact of the Metronidazole-Ciprofloxacin mixture, focusing on its molecular mechanism by examining its ability to target the Ras-MAPK signaling pathway. Methods: The MTT assay evaluated the anticancer and safety properties of a Metronidazole-Ciprofloxacin mixture. HeLa cells and human-derived adipose tissue (NHF) cell lines were used in two incubations for 24 and 72 hours, with concentrations ranging from 0.1 to 1000 µg/ml for each treatment. Cisplatin was employed for comparative purposes. The combination index CI and the selective toxicity index SI were used to assess the possible synergistic effects of the mixture’s ingredients and selective toxicity. Computational molecular docking simulations were utilized to investigate the binding affinity of the mixture ingredients to various kinase signal proteins within the MAPK-RAS pathway. Results: The MTT assay demonstrated that metronidazole, ciprofloxacin, cisplatin, and the mixture inhibit cervical cancer growth, with the mixture having a significantly greater impact than the others. The mixture showed a lesser effect on the viability of the NHF cell line and exhibited a favorable selectivity index compared to cisplatin. Additionally, the CI suggests that the medications act synergistically when used together. The molecular docking study revealed that the optimal interactions were between ciprofloxacin and RAS GTPase, and metronidazole and ERK2 kinase, with docking scores of -7.3 kcal/mol and -6.3 kcal/mol, respectively. Conclusion: Regarding the study outcomes and the well-known pharmacokinetic and safety profiles of the mixture ingredients, the metronidazole-ciprofloxacin mixture presents an attractive and safer alternative for treating cervical cancer.